How does road networks impact cultivated land multifunctionality? The role of land fragmentation: evidence from Hubei Province, China - Liu, Fan; Hu, Weiyan; Min, Min; Liu, Tian; Li, Shixiang; Rong, Qi (Frontiers in Sustainable Food Systems, 2025)
Understanding the influence mechanisms of road networks on cultivated land multifunctionality (CLM) is critical for optimizing territorial spatial patterns and achieving sustainable cultivated land resource management. This study considers the mediating role of cultivated land fragmentation (CLF) and constructs an analytical framework of “road networks–CLF–CLM” to investigate the impact of road network accessibility and transfer capacity on CLM in Hubei Province from 2013 to 2022. The results show that: (1) The enhancement of road network accessibility and transfer capacity significantly improved the overall level of CLM, promoting production function and landscape cultural function but inhibiting ecological function. (2) CLF plays a masking role in the relationship between road networks and CLM, weakening the positive impact of road networks on the overall CLM. Specifically, CLF exerted negative effects on production function and ecological function but a positive effect on landscape cultural function. (3) The influence of road networks on CLM exhibits variability across major function-oriented zones (MFOZs). These findings provide a theoretical basis for collaborative among transportation, territorial, and agricultural departments to develop differentiated road network optimization plans and zoning strategies for CLF management, thereby promoting synergistic enhancement of CLM.